Spatial Analysis of Acute Respiratory Infection (ARI) Based On the Air Pollution Standard Index (PSI) at DKI Jakarta Region in 2018-2019 - Istianah Surury; Melikhatun Azizah; Nastiti Dyah Prastiwi (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: Acute respiratory infection (ARI) is a health problem causing global morbidity and mortality in Indonesia, with 18.8 billion cases and more than six million deaths observed in 2016. Between 2013 and 2018, the diagnosis of ARI prevalence reportedly experienced a 10% decrease from 12.5-2.5%, within 10 provinces, including DKI Jakarta, Indonesia. Methods: This study aims to identify the spatial analysis of ARI events using an ecological method, based on the Air Pollution Standard Index (PSI) at DKI Jakarta between 2018 and 2019. Results and Discussion: Data analysis was performed by mapping case description through Quantum GIS, correlation assessment, as well as linear regression with SPSS scatter plot. Based on the bivariate analysis, the correlation assessment and linear regression of the ARI event with PM10 had positive regression in 2018 and 2019, at (R)0.649 and (R)0.0630, respectively. Conclusion: The highest PM10 values in Kelapa Gading and Cipayung districts increased the case of ARI fluctuations within two years. Therefore, the environmental health service office focused on the air quality evaluation and prevention control of ARI cases.